The Role of Antidepressants in a Malignancy Patient with Palliative Care: A Systematic Literature Review - Yovanda, Ryandri; Arina Widya Murni; Widya Deli Satuti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Depression is a common complication in malignancy patients, and can worsen their quality of life and prognosis. Palliative care aims to improve the quality of life of patients with life-limiting illnesses, and antidepressants are often used in this context. Methods: This systematic review was conducted to evaluate the effectiveness of antidepressants in malignancy patients with palliative care. A literature search was conducted in three databases: PubMed, Cochrane, and ScienceDirect. Search terms included “Antidepressants,” “Malignancies,” and “Palliatives.” Results: Two studies met inclusion criteria: First study: Randomized controlled clinical trial evaluating the effectiveness of mirtazapine compared with escitalopram in malignant patients with depression. The results showed that mirtazapine was more effective in improving quality of life and reducing depressive symptoms compared with escitalopram. Second study: a study evaluating the effectiveness of antidepressants in elderly malignancy patients with depression. The results suggest that antidepressants may be effective in reducing depressive symptoms and improving quality of life, but further research is needed to confirm their effectiveness and safety. Conclusion: Available evidence suggests that antidepressants may be effective in treating depression in malignancy patients with palliative care. However, further research is needed to identify the most effective and safe antidepressants for this patient population.